Longitudinal Invariance Testing Of The Knee Injury Osteoarthritis Outcome Score For Joint Replacement Scale (KOOS-JR) - Alexandra Dluzniewski; Caleb Allred; Madeline P Casanova; Jonathan D Moore; Adam C Cady; Russell T Baker (North American Sports Medicine Institute, 2023)
# Background The Knee Osteoarthritis Outcome Score for Joint Replacement (KOOS-JR) is a seven-item patient reported outcome measure used to assess perceived knee health. Though commonly used, the longitudinal psychometric properties of the KOOS-JR have not been established and further characterization of its structural validity and multi-group invariance properties is warranted. # Purpose The purpose of this study was to evaluate psychometric properties of the KOOS-JR in a large sample of patients who received care for knee pathology. # Study Design Original research. # Methods Longitudinal data extracted from the Surgical Outcome System (SOS) database of 13,470 knee pathology patients who completed the KOOS-JR at baseline, three-months, six- months, and one-year. Scale structure was assessed with confirmatory factor analysis (CFA), while multi-group and longitudinal invariance properties were assessed with CFA-based procedures. Latent group means were compared with statistical significance set at α ≤ .05 and Cohen's d effect size as d = 0.2 (small), d = 0.5 (medium), and d = 0.8 (large). # Results CFA results exceeded goodness-of-fit indices at all timepoints. Multi-group invariance properties passed test requirements. Longitudinal analysis identified a biased item resulting in removal of item #1; the retained six-item model (KOOS-JR-6) passed longitudinal invariance requirements. KOOS-JR-6 scores significantly changed over time (p ≤ .001, Mdiff = 1.08, Cohen's d = 0.57): the highest scores were at baseline examination and the lowest at 12-month assessment. # Conclusions The KOOS-JR can be used to assess baseline differences between males and females, middle and older aged adults, and patients receiving total knee arthroplasty or non-operative care. Caution is warranted if the KOOS-JR is used longitudinally due to potential measurement error associated with item #1. The KOOS-JR-6 may be a more viable option to assess change over time; however, more research is warranted. # Level of Evidence 3 © The Author(s)